GENETICS, GENOMICS AND BREEDING FOR DISEASE RESISTANCE IN POULTRY - R. Richard Churchil (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The diseases in poultry cause huge losses in the form of mortality in acute infections or as substandard performance due to chronic illness. Biosecurity and vaccination are considered as two important primary strategies for disease prevention in poultry. On the other hand, breeding for disease resistance is an alternate strategy to combat the damages of diseases. Although, attempts were initiated to develop disease resistant poultry by breeding almost a century before, this branch of science renewed the interest among scientists because of catastrophic emerging and reemerging diseases like Avian influenza. It has proven over a period of time that poultry exhibits genetic resistance to viral diseases like avian leukosis complex, Marek’s disease, avian influenza and Newcastle disease, bacterial disease like salmonellosis and may parasitic infestations. The key genes responsible for resistance to specific diseases have also been demonstrated. The breeding attempts for developing disease resistant poultry has yielded positive results with varying degree of success. The advent of sophisticated molecular methods like genomic selection using highdensity SNP chips, RNA-seq technique and identification of key marker genes and transgenesis could complement the conventional breeding methods to a larger extent in developing disease resistant poultry.